Input‐series output‐parallel DC–DC converter based on adaptive coefficient voltage equalization control. (16th June 2022) - Tang, Yu; Zhao, Zixiang; Shi, Zhe; Guo, Yingjun; Sun, Hexu
Summary: With the rapid development of power electronics technology, modular series‐parallel structures have attracted more and more attention due to high reliability and good redundancy. Especially in the occasion of high input voltage and low output voltage, the input‐series output‐parallel (ISOP) DC–DC converter is applied to reduce the stress of the device. Although this modular approach has many advantages, there is a problem of unbalanced voltage and current caused by component parameter errors in each module. Therefore, this paper proposes an inverse droop control equalization method based on coefficient adaptation. This method can not only keep the input voltage sharing (IVS) of the modules among the ISOP system but also solve the problem of the deviation of the traditional inverse droop control output voltage from the reference value, which increases the dynamic response of the system. This article first introduces the principle and control logic of the method and builds a three‐way module ISOP circuit. The experiment verifies the input voltage equalization effect and dynamic performance of the control method on the ISOP system under various working conditions. Abstract : This paper proposes an inverse droop control equalization method based on coefficient adaptation. This method can not only keep the input voltage sharing (IVS) of the modules among the ISOP system, but also solve the problem of the deviation of the traditional inverse droop control output voltage from the reference value, which increases the dynamic response of the system.